Christopher H. Pyle: CONUS Intelligence: The Army Watches Civilian Politics. ; Christopher H. Pyle: CONUS Revisited: The Army Covers up. - Johnson G. C., Charles W. (Revista Mexicana de Sociología, 2024)
-